STUDENTS MATHEMATICAL LITERACY VIEWED FROM CURIOSITY IN PROBLEM BASED LEARNING - Nugroho, Ahmad Halimy; Sukestiyarno, Sukestiyarno; Kharisudin, Iqbal (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2026)
Mathematical literacy may be described as the capacity of an individual to comprehend, mobilize, and communicate mathematical reasoning across diverse life situations in order to resolve problems meaningfully. One instructional approach frequently associated with strengthening this competence is Problem-Based Learning (PBL), which situates students within authentic problem scenarios and compels active reasoning engagement rather than passive reception. The present inquiry intends to explore and portray students’ mathematical literacy achievement through E-Module-supported PBL, interpreted through the stratification of students’ curiosity levels. The research method used is qualitative descriptive. This study analyzes and describes students’ mathematical literacy abilities based on categories of student curiosity. The research subjects involved 10th-grade PM 2 students at SMKN 1 Kendal for the 2024/2025 academic year. Empirical findings indicate that learners categorized with elevated curiosity demonstrate mastery across all mathematical literacy indicators, whereas those within moderate and low curiosity tiers exhibit constraints particularly during interpretation and evaluative stages of solution processes. These results accentuate the salience of affective disposition especially curiosity in maximizing mathematical literacy within problem-based environments.